Pengaruh Kemahiran Profesional, Independensi, dan Objektivitas Terhadap Kualitas Audit (Studi Kasus pada Inspektorat Jenderal Kemendikbudristek) - Syaparudin, Syaparudin; Apollo, Apollo (Jurnal Ilmu Multidisiplin, 2023)
Auditor quality must meet aspects such as professional skills, independence, objectivity and several other aspects inherent in their profession. This is to maintain the quality of audit results, for corporate entities as well as for public entities. This research was conducted to determine the Effect of Professional Proficiency, Independence, and Objectivity on Audit Quality (Case Study of auditors within the Inspectorate General of the Ministry of Education and Culture). Respondents in this study were 122 respondents. The data used in this study is primary data, namely in the form of a questionnaire. This research uses multiple linear analysis and partial test as well as simultaneous test using a data processing application. The results of this study indicate that professional skills affect audit quality, independence influences audit quality, and objectivity influences audit quality.